Role of certain growth factors and hormones in folliculogenesis - KHARCHE, SURESH DINKAR; JENA, DAYANIDHI; GANGWAR, CHETNA; KHATTI, AMIT; BALAMURUGAN, B (The Indian Journal of Animal Sciences, 2020)
Folliculogenesis is an inextricable process associated with female fertility and infertility cases. This process involves many events at cellular and molecular level in a highly orchestrated fashion which culminates with ovulation. Various factors like hormonal factors, growth factors, role of ovarian micro environment, diseases of reproductive tract etc. influence the process of folliculogenesis in systematic manner. The function and mechano-biology of these growth factors and hormones have been studied by many researchers. This review discusses about those hormonal and growth factors which are involved in folliculogenesis process.